2020
DOI: 10.1002/alz.12172
|View full text |Cite|
|
Sign up to set email alerts
|

36‐month LipiDiDiet multinutrient clinical trial in prodromal Alzheimer's disease

Abstract: Introduction: The LipiDiDiet trial investigates the effects of the specific multinutrient combination Fortasyn Connect on cognition and related measures in prodromal Alzheimer's disease (AD). Based on previous results we hypothesized that benefits increase with long-term intervention. Methods: In this randomized, double-blind, placebo-controlled trial, 311 people with prodromal AD were recruited using the International Working Group-1 criteria and assigned to active product (125 mL once-a-day drink) or an isoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
98
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 32 publications
7
98
0
1
Order By: Relevance
“…The study was likely underpowered to detect these differences. Another explanation for these findings is that the changes, especially in NTB, were modest overall and lower than expected during the first 2 years of the LipiDiDiet trial [17] but closer to the expectation after 3 years [35]. Here, we observed that the changes were fairly small even among those with both abnormal Aβ and neuronal injury markers.…”
Section: Discussionsupporting
confidence: 77%
“…The study was likely underpowered to detect these differences. Another explanation for these findings is that the changes, especially in NTB, were modest overall and lower than expected during the first 2 years of the LipiDiDiet trial [17] but closer to the expectation after 3 years [35]. Here, we observed that the changes were fairly small even among those with both abnormal Aβ and neuronal injury markers.…”
Section: Discussionsupporting
confidence: 77%
“…Hence, there is justification for the use of supplements, either in the form of nutraceuticals or functional foods, to slow cognitive decline [2]. Some products are, indeed, available in the market and have been tested with equivocal results [30]. It must be underscored that there are several hurdles to overcome when fatty acids are tested in the cardiovascular or neurological arenas [31].…”
Section: Discussionmentioning
confidence: 99%
“…Fear conditioningConditioning and testing took place in a rodent observation cage using a shock generator (model LI100-26 Shocker, LETICA I.C., Madrid, Spain). The observation cage(30 x 37 x 25 cm) was placed in a sound-attenuating chamber. The side walls of the observation cage were constructed of stainless steel and the back walls and doors were constructed ofclear Plexiglass.…”
mentioning
confidence: 99%
“…The FINGER study is a randomised controlled trial with a multidomain intervention consisting of a 2 years intervention including diet, exercise, cognitive training and vascular risk monitoring, which demonstrated that this multidomain approach could improve or maintain cognitive functioning in at-risk elderly people [115]. Two years later, a 24-month multicentre trial in which prodromal Alzheimer's patients received a specific multinutrient showed that they had better results on the cognitive-functional measurements and less brain atrophy as assessed by magnetic resonance imaging (MRI) [116].…”
Section: Healthy Aging Brain As Prevention For Neurodegenerative Disementioning
confidence: 99%